Agnosia integrativa causada por una epilepsia focal occipital izquierda: estudio de caso (2011)
Integrative agnosia is a type of visual agnosia associated with bilateral occipital lesions and characterized by the inability to identify stimuli in complex backgrounds, especially when it comes to overlapping or interlocking shapes. There are difficulties in coding and grouping the whole from the parts of the stimulus. We report a case of a 14 year-old female, with integrative agnosia as consequence of refractory symptomatic focal epilepsy with left occipital epileptogenic focus. Clinical features and the visual recognition processes are analyzed and discussed from different theoretical models that attempt to explain visual perception.